2009
DOI: 10.1017/s1481803500011118
|View full text |Cite
|
Sign up to set email alerts
|

Individual emergency physician admission rates: predictably unpredictable

Abstract: Objective: We sought to determine the degree and possible causes of variability in admission practices among individual emergency physicians (EPs) at 1 emergency department (ED) using a Canadian Emergency Department Triage Acuity Scale (CTAS)-matched ED patient population. Methods: We distributed a survey measuring attitudes and demographics to all EPs (n = 30) at a large regional hospital. Hospital admissions data from 1 calendar year were matched to individual EP survey results. Emergency physicians were ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
9
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 11 publications
(10 reference statements)
0
9
0
Order By: Relevance
“…After adjusting for patient and clinical characteristics, admission rates varied from 21% to 49% among physicians and from 27% to 41% among 3 facilities. Two other studies from single hospitals have found similar variation among providers . The reasons for the variation among ED providers presumably relate to subjective aspects of clinical assessment and the reluctance of providers to rely solely on objective scales, even when they are available .…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…After adjusting for patient and clinical characteristics, admission rates varied from 21% to 49% among physicians and from 27% to 41% among 3 facilities. Two other studies from single hospitals have found similar variation among providers . The reasons for the variation among ED providers presumably relate to subjective aspects of clinical assessment and the reluctance of providers to rely solely on objective scales, even when they are available .…”
Section: Discussionmentioning
confidence: 82%
“…Two other studies from single hospitals have found similar variation among providers . The reasons for the variation among ED providers presumably relate to subjective aspects of clinical assessment and the reluctance of providers to rely solely on objective scales, even when they are available . Variation in admission rates among different facilities may relate to clustering of providers with similar practice styles within facilities, lack of clinical guidelines for certain conditions, as well as differences among facilities in the socioeconomic status and access to primary care of their clientele .…”
Section: Discussionmentioning
confidence: 87%
“…It is possible that with greater experience comes a greater appreciation for unanticipated outcomes, or that physicians are simply more likely to experience a lawsuit the longer they practice. Previous studies have been mixed in terms of the impact of physician experience on levels of testing and admission 10,36,37. Further work will be necessary to clarify the exact impact and role of experience, how it differs for different clinical conditions, and how it interacts with risk tolerance.…”
Section: Discussionmentioning
confidence: 99%
“…Interventions that target practice variation in diagnostic imaging could improve healthcare delivery and reduce health care costs, cancer risk due to exposure to ionizing radiation, and downstream effects of incidental findings . In particular, there is significant variation in emergency physician utilization of computed tomography (CT) imaging, but the underlying causes of this variation remain unclear . Previous studies have suggested that physician characteristics, such as differences in physician risk tolerance or perceived malpractice risk, may account for the variation in emergency department (ED) decision‐making …”
mentioning
confidence: 99%